Effects of galvanic vestibular stimulation on resting state brain activity in patients with bilateral vestibulopathy. Issue 9 (27th February 2020) - Helmchen, Christoph; Machner, Björn; Rother, Matthias; Spliethoff, Peer; Göttlich, Martin; Sprenger, Andreas
Abstract: We examined the effect of galvanic vestibular stimulation (GVS) on resting state brain activity using fMRI (rs‐fMRI) in patients with bilateral vestibulopathy. Based on our previous findings, we hypothesized that GVS, which excites the vestibular nerve fibers, (a) increases functional connectivity in temporoparietal regions processing vestibular signals, and (b) alleviates abnormal visual–vestibular interaction. Rs‐fMRI of 26 patients and 26 age‐matched healthy control subjects was compared before and after GVS. The stimulation elicited a motion percept in all participants. Using different analyses (degree centrality, DC; fractional amplitude of low frequency fluctuations [fALFF] and seed‐based functional connectivity, FC), group comparisons revealed smaller rs‐fMRI in the right Rolandic operculum of patients. After GVS, rs‐fMRI increased in the right Rolandic operculum in both groups and in the patients' cerebellar Crus 1 which was related to vestibular hypofunction. GVS elicited a fALFF increase in the visual cortex of patients that was inversely correlated with the patients' rating of perceived dizziness. After GVS, FC between parietoinsular cortex and higher visual areas increased in healthy controls but not in patients. In conclusion, short‐term GVS is able to modulate rs‐fMRI in healthy controls and BV patients. GVS elicits an increase of the reduced rs‐fMRI in the patients' right Rolandic operculum, which may be an important contribution to restore the disturbed visual–vestibular interaction. The GVS‐induced changes in the cerebellum and the visual cortex were associated with lower dizziness‐related handicaps in patients, possibly reflecting beneficial neural plasticity that might subserve visual–vestibular compensation of deficient self‐motion perception.